2012
DOI: 10.5585/gep.v3i2.118
|View full text |Cite
|
Sign up to set email alerts
|

O Pregão Eletrônico como Instrumento de Controle de Oportunismos no Processo Licitatório Público

Abstract: Este trabalho tem como objetivo analisar a operação de pregão eletrônico (PE) no sistema Comprasnet, da União, que busca instrumentalizar o governo para lidar com o oportunismo dos licitantes, permitindo ao primeiro, contratar bens e serviços a preços mais compatíveis com os praticados no mercado.O desenho da pesquisa envolve o estudo de caso, em nível descritivo, dos processos de PE no sistema Comprasnet, do Governo Federal, tendo como campo de pesquisa uma área demandante e cinco pregoeiros como sujeitos soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
2
Order By: Relevance
“…With this, we observed that market prices in the quotation are higher than prices in the electronic auction, that is, the bidding process in the electronic auction modality allows a price difference between the items when compared with the market prices. This fact is explained in Oura et al (2012), in which companies can substantially burden the values in the preparation phase of the bidding, in order to obtain additional profits when the bidding process occurs, that is, the companies that provide reference price budgets participate in the bidding contest offering prices below the estimated value, this fact is credited to the opportunism of the bidder, or the supplier. As stated by Faria et al (2010), most suppliers seek to increase the frequency of transactions by creating more favorable pricing policies for known public agencies, the frequency of transactions is also advantageous for the bidder, since the accumulation of information on the bidder agency allows the reduction of costs associated with the unpredictability of the negotiation, inducing a lower price to gain competition.…”
Section: Resultsmentioning
confidence: 99%
“…With this, we observed that market prices in the quotation are higher than prices in the electronic auction, that is, the bidding process in the electronic auction modality allows a price difference between the items when compared with the market prices. This fact is explained in Oura et al (2012), in which companies can substantially burden the values in the preparation phase of the bidding, in order to obtain additional profits when the bidding process occurs, that is, the companies that provide reference price budgets participate in the bidding contest offering prices below the estimated value, this fact is credited to the opportunism of the bidder, or the supplier. As stated by Faria et al (2010), most suppliers seek to increase the frequency of transactions by creating more favorable pricing policies for known public agencies, the frequency of transactions is also advantageous for the bidder, since the accumulation of information on the bidder agency allows the reduction of costs associated with the unpredictability of the negotiation, inducing a lower price to gain competition.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Williamson (1985), no processo de negociação, uma das partes ou ambas as partes estão vulneráveis a atitudes oportunistas, visto que existe tendência à concentração de informações privilegiadas. Alguns estudos (Faria et al, 2010;Ahimbisibwe et al, 2012;Oura et al, 2012;Juricik, 2014) apontam que o oportunismo em processos licitatórios evidencia riscos existentes nos mesmos, abordando os atributos da teoria dos custos de transação.…”
unclassified
“…A eficácia do Pregão Eletrônico no Comprasnet, na eliminação do oportunismo dos licitantes, foi verificada por Oura et al (2012). Os autores concluíram que embora existam melhoras nas contratações por intermédio do PE, " [...] o uso isolado do PE parece não ser suficiente para coibir ações de oportunismo que, se não podem ser caracterizadas diretamente como fraudes premeditadas, beiram perigosamente esses princípios" (OURA et al 2012, p. 278).…”
unclassified